Characterization of silk genes in Ephestia kuehniella and Galleria mellonella revealed duplication of sericin genes and highly divergent sequences encoding fibroin heavy chains - Wu, Bulah Chia-hsiang; Sauman, Ivo; Maaroufi, Houda Ouns; Zaloudikova, Anna; Zurovcova, Martina; Kludkiewicz, Barbara; Hradilova, Miluse; Zurovec, Michal (Frontiers in Molecular Biosciences, 2022)
Silk is a secretory product of numerous arthropods with remarkable mechanical properties. In this work, we present the complete sequences of the putative major silk proteins of E. kuehniella and compare them with those of G. mellonella, which belongs to the same moth family Pyralidae. To identify the silk genes of both species, we combined proteomic analysis of cocoon silk with a homology search in transcriptomes and genomic sequences to complement the information on both species. We analysed structure of the candidate genes obtained, their expression specificity and their evolutionary relationships. We demonstrate that the silks of E. kuehniella and G. mellonella differ in their hydrophobicity and that the silk of E. kuehniella is highly hygroscopic. In our experiments, we show that the number of genes encoding sericins is higher in G. mellonella than in E. kuehniella. By analysing the synteny of the chromosomal segment encoding sericin genes in both moth species, we found that the region encoding sericins is duplicated in G. mellonella. Finally, we present the complete primary structures of nine fibH genes and proteins from both families of the suborder Pyraloidea and discuss their specific and conserved features. This study provides a foundation for future research on the evolution of silk proteins and lays the groundwork for future detailed functional studies.